How do Italian-speaking children handle wh-questions? A comparison between children with hearing loss and children with normal hearing. (2nd April 2020) - D'Ortenzio, Silvia; Volpato, Francesca
ABSTRACT: In this paper, we analyse how Italian-speaking children with cochlear implants produce subject and object questions introduced by who and which +NP. The aim of the study is to analyse whether a correlation exists between the accuracy of the responses of an elicitation task of wh -questions and clinical variables (i.e. age of hearing aid fitting; age of cochlear implantation; duration of hearing experience) in a group of children with cochlear implants, in order to provide new evidences in support of the efficacy of early intervention in Italian-speaking children with hearing loss. The experimental group was composed of 10 children fitted with a cochlear implant, who were diagnosed and promptly fitted with hearing aids within the first year of life. All these participants received a cochlear implant when hearing aids did not provide enough auditory input anymore. Indeed, while the hearing aids only amplify sounds, cochlear implants directly stimulate the auditory nerve providing better auditory perception. Results were compared with those of two control groups. The first group was composed of 10 children with normal hearing and comparable chronological age, while the second group was composed of 10 children with normal hearing matched on comparable hearing experience. Children were assessed with a test for the elicitation of subject and object who and which +NP questions. Results show that the two control groups performed better than the experimental group. Moreover, some correlations were found between the accuracy of the production of complex structures and the age of fitting of the hearing aids and the hearing experience.